Susceptibility of table grape varieties grown in south‐eastern Italy to Drosophila suzukii. (18th January 2018) - Baser, N.; Broutou, O.; Verrastro, V.; Porcelli, F.; Ioriatti, C.; Anfora, G.; Mazzoni, V.; Rossi Stacconi, M. V.
Abstract: Since 2008, Drosophila suzukii, the spotted wing drosophila, has colonized most of the American and European continents, being able to adapt to very different climates. In Italy, this pest has been captured from northern Alpine to southern Mediterranean regions where it can infest a broad range of fruits, including wine grapes. Studies have shown that oviposition levels and developmental rates of D. suzukii on wine grapes are lower than on other berries, although recent observations indicate that grapes may become a suitable host plant in particular conditions. Here, we report, for the first time, the results of a series of no‐choice oviposition experiments using berries of five table grape varieties sampled in the provinces of Taranto and Bari (Apulia region, south‐eastern Italy) during 2013 from both organic and conventional farming systems. The sugar content (SC) and skin hardness of each sample were analysed to assess the influence of these physiological parameters on the susceptibility of table grapes to D. suzukii infestation. A negative correlation was found between the number of eggs laid and berry skin penetration force, whereas there was a positive one between the number of eggs and Brix values, as well as sampling date. In organic grapes, SC and skin hardness of two varieties ("Crimson" and "Scarlotta") were measured, respectively, higher and lower than in conventional grapes, thus making them more susceptible to pest infestation. The study hence shows that in laboratory conditions D. suzukii is able to heavily infest and develop on table grapes and that susceptibility to its infestation significantly depends on both variety and farming system.